2012
DOI: 10.1017/s0007114512002127
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Mexican food photograph album as a tool to visually estimate food amounts in adolescents

Abstract: The aim of the present study was to validate a food photograph album (FPA) as a tool to visually estimate food amounts, and to compare this estimation with that attained through the use of measuring cups (MC) and food models (FM). We tested 163 foods over fifteen sessions (thirty subjects/session; 10-12 foods presented in two portion sizes, 20 -24 plates/session). In each session, subjects estimated food amounts with the assistance of FPA, MC and FM. We compared (by portion and method) the mean estimated weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…The administration, analysis and data interpretation of these tools are time-consuming, as they entail the use of mechanisms such as food surveys, 24-h reminders, food records or semiquantitative food frequency questionnaires in order to study dietary factors such as adequacy, balance, variety, safety, and so on [5,18]. With 24-h recalls and semiquantitative food frequency questionnaires, cognitive functions such as conceptualization (the ability to make a mental construction of a particular amount of food not present) and memory (the ability to remember the amount ingested) may lead to confusion in the subject and contribute to potential sources of error in estimating quantities, which do not allow the accuracy of the tool used to be assessed with a risk of under-reporting bias to be present [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration, analysis and data interpretation of these tools are time-consuming, as they entail the use of mechanisms such as food surveys, 24-h reminders, food records or semiquantitative food frequency questionnaires in order to study dietary factors such as adequacy, balance, variety, safety, and so on [5,18]. With 24-h recalls and semiquantitative food frequency questionnaires, cognitive functions such as conceptualization (the ability to make a mental construction of a particular amount of food not present) and memory (the ability to remember the amount ingested) may lead to confusion in the subject and contribute to potential sources of error in estimating quantities, which do not allow the accuracy of the tool used to be assessed with a risk of under-reporting bias to be present [19].…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, a tool called the Mini Food Intake Quality Survey (Mini-ECCA), whose structure was similar to that of indices which measured adherence to the Mediterranean diet and included photographs as a visual reference to estimate quantity, as they present lower food quantity estimation error than other visual support tools [19], provided a rapid assessment of food intake quality as indicated by adherence to intake recommendations. This survey produced good levels of reproducibility (ρ = 0.713, p < 0.001; ICC = 0.844, 95% CI, 0.793-0.883) and moderate levels of agreement in terms of food intake quality classification (κ = 0.545, 95% CI, 0.484 to 0.606, p < 0.001), and thus proved to be suitable for dietary evaluation and guidance purposes [26].…”
Section: Introductionmentioning
confidence: 99%
“…(13, 37). However, a study in South Africa (18) showed that accuracy of estimation was not affected by sex, age, or education. The estimated size of the portions was not influenced by sex and BMI of the individuals and that it was easier to estimate the portions of food that are habitual (35).…”
Section: Discussionmentioning
confidence: 97%
“…Food photographs depicting standardized portion sizes organized in an atlas are helpful in improving the accuracy of food quantification (17, 18). The number and size of photographs vary from one to eight among studies.…”
mentioning
confidence: 99%
“…In the absence of pre-existing data, portion size ranges have been deduced by various means, such as by 66 adapting from local reference data (e.g., dietary guidelines and nationally established standard serving 67 sizes), consulting experts in the catering industry, qualitative consultation with households [9][10][11], or 68 deriving a medium portion size from existing survey data but applying fixed ratios to derive small and 69 large portion sizes [9,12]. In some studies to develop and validate food photo atlases, either very scant or 70 no information was provided on how graduated portion sizes were derived [10,13,14], confirming that 71 this methodological step is often overlooked. This is concerning as, if portion size options presented in 72 SQ-FFQ or SQ-24HR dietary assessment surveys do not represent the usual range consumed in the 73 population studied, large portion size estimation errors can result [15].…”
mentioning
confidence: 99%